Heterogeneity of virological suppression in the national antiretroviral programme of Cameroon (ANRS 12288 EVOLCAM). Issue 1 (25th October 2018) - Liégeois, F; Eymard‐Duvernay, S; Boyer, S; Maradan, G; Kouanfack, C; Domyeum, J; Boyer, V; Mpoudi‐Ngolé, E; Spire, B; Delaporte, E; Vidal, L; Kuaban, C; et al.
Abstract : Objectives: In terms of HIV infection, western and central Africa is the second most affected region world‐wide, and the gap between the regional figures for the testing and treatment cascade and the Joint United Nations Programme on HIV/AIDS (UNAIDS) 90–90–90 targets is particularly worrying. We assessed the prevalence of virological suppression in patients routinely treated in 19 hospitals in Cameroon. Methods: A cross‐sectional survey was performed in adult patients receiving antiretroviral therapy (ART) in the Centre and Littoral regions. The prevalences of virological suppression (<1000 HIV‐1 RNA copies/mL) were compared among all 19 hospitals using the χ 2 test. Potential individual and health care‐related determinants of virological suppression were assessed using multivariate logistic regression models. Results: A total of 1700 patients (74% women; median age 41 years; median time on ART 3.7 years) were included in the study. The prevalence of virological suppression was 82.4% overall (95% confidence interval 80.5–84.2%). It ranged from 57.1 to 97.4% according to the individual hospital ( P < 0.001). After adjustment, virological suppression was associated with age, CD4 cell count at ART initiation, disclosure of HIV status to family members, interruption of ART for more than two consecutive days, and location of patient's residence and hospital (rural/urban). These factors did not explain the heterogeneity of virological suppression between the study hospitals ( P < 0.001). Conclusions: The overall prevalence of virological suppression was reassuring. Nevertheless, the heterogeneity of virological suppression among hospitals highlights that, in addition to programme‐level data, health facility‐level data are crucial in order to tailor the national AIDS programme's interventions with a view to achieving the third UNAIDS 90 target.